RECENT ADVANCES IN MODELLING AND OPTIMIZING COMPLEX SYSTEMS BASED ON INTELLIGENT ALGORITHMS - Li, Yuhong; Gong, Guanghong; Li, Ni (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
The paper tries to understand recent research advances in modelling and optimizing complex systems to give references for interested researchers. Intelligent models have the capability of self-adapting to the changing environment, which may generate effective solutions for complex dynamic systems. Firstly, critical techniques and significant events in the development process of complex systems are reviewed. Then classical practical applications of modelling and optimizing complex systems over recent years based on several representative intelligent models are introduced and analysed. Thirdly, methodology of each intelligent M & O model is analysed and compared. Finally, this paper concludes and prospects relevant future work.